1997
DOI: 10.1073/pnas.94.14.7572
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and activity of antioxidant enzymes after ionizing irradiation in radiation-resistant and radiation-sensitive mice

Abstract: The involvement of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase in radiobiological processes has been described at the enzyme activity level. We irradiated radiationresistant (RR) and radiation-sensitive (RS) mice and studied antioxidant enzymes at the transcriptional and activity level. In addition, aromatic hydroxylation and lipid peroxidation parameters were determined to study radiation resistance at the oxidation level. RS BALB͞c͞J Him mice and RR C3H He͞H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 35 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…p53 protein can activate an ionizing radiation-dependent apoptotic pathway in tissue known to be acutely sensitive to radiation in vivo (Macleod et al, 1995). In addition to p53 and other components of the DNA-damage repair pathway including scid and PARP (Biedermann et al, 1991;Wesierska-Gadek et al, 1999), two factors implicated in oxidative stress-responses and which regulate the rates of irradiation injury include Superoxide Dismutase and Catalase (Hardmeier et al, 1997). Ionizing radiation induces damage not only to DNA but to lipids and proteins in part from the generation of highly reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…p53 protein can activate an ionizing radiation-dependent apoptotic pathway in tissue known to be acutely sensitive to radiation in vivo (Macleod et al, 1995). In addition to p53 and other components of the DNA-damage repair pathway including scid and PARP (Biedermann et al, 1991;Wesierska-Gadek et al, 1999), two factors implicated in oxidative stress-responses and which regulate the rates of irradiation injury include Superoxide Dismutase and Catalase (Hardmeier et al, 1997). Ionizing radiation induces damage not only to DNA but to lipids and proteins in part from the generation of highly reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicated that irradiation results in increased endogenous MnSOD-mRNA as well as increased MnSOD biochemical activity following irradiation. 19,20 Ionizing irradiation induces expression of NFk-B, and its activation of the promoter for the MnSOD gene may be the mechanism of increased endogenous MnSOD expression. 21,22 Administration of HA-MnSOD-PL in previous studies was as protective as non-tagged MnSOD with respect to decreased irradiation relative to organizing alveolitis and persistent biochemical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that extracellular SOD is up-regulated along with inducible nitric oxide synthase after nuclear factor-κB (NF-κB) activation [12]. Hardmeier et al [13] reported that SOD activities were also increased at a very early post-irradiation period. The ACE1…”
Section: Introductionmentioning
confidence: 98%